Familial malignant osteopetrosis in children: A case report - Gomes, Monica Fernandes [UNESP]; Rangel, Daniela Coelho [UNESP]; Starling, Cláudia Cristina Morais; Goulart, Maria Das Graças Vilela [UNESP] (Wiley, 2006)
The clinical, radiological, pathological and laboratory findings of two brothers with autosomal recessive malignant osteopetrosis are presented. Our findings are similar to characteristics previously reported in the literature about patients with osteopetrosis. The 6-year-old male patient was pale and had petechiae on his arms and legs. He also had macrocephalia, splenomegaly, severe pancytopenia, genu valgus, hypocalcemia, amaurosis, cessation of physical development, generalized bone sclerosis and recurrent infections with a history of multiple incidences of acute otitis media. Generalized bone sclerosis and irregular sclerosis of the maxilla and mandible were seen on radiographs. The oral mucosa was apparently normal but permanent tooth eruption was delayed although there was early loss of deciduous teeth. The recommended treatment was blood transfusion and therapy with antibiotics when necessary; a bone marrow transplant was not possible due to lack of a compatible donor.
Keywords: Bone disease; Histological and radiological finding; Malignant infantile osteopetrosis; Oral manifestation; Albers Schoenberg disease; case report; child; craniofacial malformation; face asymmetry; fatality; genetics; human; jaw disease; male; preschool child; purpura; Child; Child, Preschool; Craniofacial Abnormalities; Facial Asymmetry; Fatal Outcome; Humans; Male; Mandibular Diseases; Maxillary Diseases; Osteopetrosis; Purpura